(untitled) (Vietnam Journal of Community Medicine, 2026)
Objective: To describe nurses’ perceptions of leadership styles and effectiveness of their direct supervisors. Methods: A cross-sectional descriptive study was conducted among 317 nurses enrolled in the first-level specialization program at Nam Dinh University of Nursing. Data were collected from February to March 2023 using the self-administered Multifactor Leadership Questionnaire – Form 5X. Results: Nurses most commonly reported the use of Conditional Reward (3.90 ± 0.73), Intellectual Stimulation (3.84 ± 0.76), and Idealized Influence–Behavior (3.81 ± 0.73) leadership behaviors. Conversely, Laissez-faire leadership (2.30 ± 0.83) and Passive Management-by-Exception (2.48 ± 0.78) were the least observed. Supervisors were also perceived to positively impact staff’s extra effort, satisfaction, and effectiveness at work. Conclusion: Nurse leaders are perceived to predominantly use active and positive leadership styles, contributing to enhanced work motivation and professional performance quality.